Solid-state lithium ion battery polymer electrolyte based on p-fluorocinnamic acid

By using the introduction of specific groups to fluorocinnamic acid in the solid-state lithium-ion battery polymer electrolyte, the energy density and safety issues of traditional lithium-ion batteries are solved, the ionic conductivity and interface stability of solid-state batteries are improved, and the cycling performance of the battery is significantly improved.

CN119890437AActive Publication Date: 2025-04-25HEFEI UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510387263.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-25
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

The energy density of traditional lithium-ion batteries is close to the limit, and the organic liquid electrolytes have poor thermal stability and high flammability, resulting in safety hazards; while the polymer electrolytes in solid lithium-ion batteries have low room temperature ion conductivity, insufficient oxidation resistance and interface stability, which affects the cycle life.

Method used

The solid lithium-ion battery polymer electrolyte is synthesized by using p-fluorocinnamic acid as one of the monomers. By introducing carboxyl groups, fluorine atoms and benzene rings, the dissociation of lithium ions in the lithium salt and the chemical stability of the polymer are enhanced, and the interface stability is enhanced.

Benefits of technology

The room temperature ion conductivity, electrochemical window and interface stability of solid-state lithium-ion batteries is significantly improved, thereby improving the cycling performance and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890437A_ABST
    Figure CN119890437A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of synthesis of high-molecular compounds and lithium ion batteries, and discloses a p-fluorocinnamic acid-based solid-state lithium ion battery polymer electrolyte, and a preparation method of the electrolyte comprises the following steps: firstly, carrying out polymerization reaction on a p-fluorocinnamic acid monomer and a carbonic ester-based monomer, and then blending the prepared product with a lithium salt and a polymer matrix to obtain the p-fluorocinnamic acid-based solid-state lithium ion battery polymer electrolyte. And heating and stirring to obtain a transparent and uniform solution, coating a polytetrafluoroethylene plate with the solution, and drying in a vacuum oven to finally obtain the p-fluorocinnamic acid-based solid-state lithium ion battery polymer electrolyte membrane. The polymer electrolyte membrane prepared by the invention has high ionic conductivity and electrochemical window, and has a remarkable effect on improving the performance of a solid-state lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer compound synthesis and lithium ion batteries, and in particular relates to a solid lithium ion battery polymer electrolyte based on p-fluorocinnamic acid. Background Art

[0002] At present, with the growing demand for portable consumer electronic devices, energy-powered vehicles, and large-scale grid energy storage systems, the market has put forward higher requirements for the energy density, safety, cycle life and other performance of lithium-ion batteries (LIBs). However, the energy density of lithium-ion batteries in traditional systems has reached its limit and it is difficult to achieve a breakthrough; and the organic liquid electrolytes used in traditional commercial lithium-ion batteries have poor thermal stability and high flammability, which may cause catastrophic fires or even explosions and other safety issues. In order to solve the above problems, all-solid-state lithium-ion batteries (ASSLIBs) have developed rapidly in recent years. ASSLIBs use non-flammable or non-combustible solid electrolytes (SSEs) to replace the organic electrolytes in the traditional system, which helps to solve the inherent safety of lithium batteries, and because the structure is more compact, ASSLIBs can have a higher energy density.

[0003] As the core component of ASSLIBs, SSEs have the dual functions of ion conduction and blocking the contact between positive and negative electrodes, and are the key factors affecting the performance of ASSLIBs. Solid electrolytes are generally divided into two categories: inorganic solid electrolytes (ISEs) and polymer solid electrolytes (SPEs). ISEs usually have excellent ionic conductivity and a wide electrochemical window, but have defects such as brittle fracture and poor interface compatibility, which seriously hinder their practical application. In contrast, although the basic electrochemical performance of SPEs is not as good as that of ISEs, they are considered to have great prospects for industrial application due to their good flexibility, easy film formation, excellent interface contact, and advantages in battery integration and processing costs.

[0004] SPEs generally conduct lithium ions through the movement of polymer chains, but polymer materials generally have high crystallinity at room temperature, which limits the free movement of chains and Li + The coordination migration of SPEs plays a limiting role, so the room temperature ionic conductivity of SPEs is generally low (<10 -4 S cm -1 ). In addition, SPEs are usually weak in oxidation resistance and cannot match high-voltage positive electrodes; the interface stability is also relatively poor, making it difficult to resist interface side reactions and lithium dendrite growth. For this reason, researchers have been continuously designing and optimizing SPEs through functional group regulation, structural optimization, interface engineering, and new preparation processes over the years to improve the ionic conductivity, electrochemical window, interface stability of polymer electrolytes, and the cycle life and stability of their batteries. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid, aiming to improve the ionic conductivity, electrochemical window and interface stability of the polymer electrolyte, thereby improving the cycle performance of the solid-state lithium-ion battery constructed based on the polymer electrolyte.

[0006] The technical solution adopted by the present invention is as follows: The present invention first provides a method for preparing a solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid, comprising the following steps: (1) adding p-fluorocinnamic acid to a polar aprotic organic solvent, heating and stirring until dissolved, to obtain solution A; (2) adding a carbonate monomer and an initiator to solution A, heating and stirring to react, and obtaining solution B; (3) Add lithium salt to solution B, heat and stir until dissolved, and obtain solution C; (4) Add the polymer matrix to solution C, heat and stir until dissolved, and obtain solution D; (5) The solution D is coated on a polytetrafluoroethylene plate, and the solvent is dried under vacuum to obtain a solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid.

[0007] Preferably, steps (1) to (4) are carried out in a normal pressure reactor protected by an inert gas atmosphere, the heating temperature is 40-80° C., and the heating and stirring reaction time in step (2) is 12-48 h.

[0008] Preferably: the mass ratio of p-fluorocinnamic acid to polar aprotic organic solvent is 1:(10-100); the molar ratio of p-fluorocinnamic acid to carbonate-based monomer is 1:(1-30), the added amount of initiator is 0.05%-1% of the total mass of p-fluorocinnamic acid and carbonate-based monomer; the molar ratio of p-fluorocinnamic acid to lithium salt is 1:(1-10); the molar ratio of p-fluorocinnamic acid to polymer matrix is ​​1:(1-10).

[0009] Preferably, in step (1), the polar aprotic organic solvent is at least one of acetonitrile, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran and dichloromethane.

[0010] Preferably, in step (2), the carbonate-based monomer is at least one of vinylene carbonate, vinyl ethylene carbonate, ethyl methacrylate and methyl acrylate.

[0011] Preferably, in step (3), the lithium salt is at least one of lithium nitrate, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(trifluoromethanesulfonylimide), lithium difluorooxalatoborate and lithium bis(fluorosulfonylimide).

[0012] Preferably, in step (4), the polymer matrix is ​​at least one of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polyvinylidene fluoride and copolymers thereof.

[0013] The present invention also provides a solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid. The solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid is prepared by the above-mentioned preparation method.

[0014] The present invention further provides a solid-state lithium-ion battery, which contains the solid polymer electrolyte based on p-fluorocinnamic acid. The preparation method of the solid-state lithium-ion battery comprises the following steps: (1) Grind the positive electrode active material, carbon black and polyvinylidene fluoride in a ratio of 8:1:1, and then disperse them in N-methylpyrrolidone solvent to obtain a paste slurry, apply it on aluminum foil with a scraper, and dry it to obtain a positive electrode sheet; (2) Using a metal lithium sheet as the negative electrode, in combination with the above-mentioned positive electrode sheet and the solid polymer electrolyte based on p-fluorocinnamic acid, a solid-state lithium-ion battery is prepared; Preferably, in step (1), the positive electrode active material is lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, or ternary material LiNi x Co y Mn z At least one of O2 (x + y + z = 1).

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention selects p-fluorocinnamic acid as one of the monomers to synthesize a solid-state lithium-ion battery polymer electrolyte. P-fluorocinnamic acid introduces carboxyl groups, fluorine atoms and benzene rings into the electrolyte system. The carboxyl group can promote the dissociation of lithium ions and anions in lithium salts through electrostatic attraction and increase free lithium ions. Highly electronegative fluorine atoms can enhance the chemical stability and oxidation resistance of the polymer, reduce the decomposition of the electrolyte under high voltage, and improve the interface stability. The benzene ring can improve the mechanical properties of the electrolyte membrane and inhibit the growth of lithium dendrites.

[0016] 2. The p-fluorocinnamic acid selected in the present invention contains conjugated double bonds, which can undergo free radical polymerization with carbonate monomers under the action of an initiator to form a new polymer structure. The rigid fluorophenyl (p-fluorocinnamic acid) is combined with the flexible carbonate segment to balance mechanical strength and flexibility.

[0017] 3. The solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid provided by the present invention has excellent performance, not only has high room temperature ionic conductivity (8.1×10 -4 S cm -1 ), and after being applied to solid-state lithium-ion batteries, it can significantly improve the capacity and cycle life of solid-state lithium-ion batteries. The preparation method is convenient and can utilize existing battery production processes and production equipment without increasing equipment investment, and has good industrialization prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is an infrared absorption spectrum of the solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid prepared in Example 1; Figure 2 This is a surface SEM image of the solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid prepared in Example 1; Figure 3 This is a surface SEM image of the solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid prepared in Example 2; Figure 4 This is a surface SEM image of the solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid prepared in Comparative Example 1; Figure 5 Impedance diagrams of solid-state lithium-ion battery polymer electrolyte membranes based on p-fluorocinnamic acid prepared in Example 1, Example 2 and Comparative Example 1; Figure 6 The lithium ion migration number diagram of the solid-state lithium ion battery polymer electrolyte membrane based on p-fluorocinnamic acid prepared in Example 1; Figure 7 The electrochemical window diagrams of the solid-state lithium-ion battery polymer electrolyte membranes based on p-fluorocinnamic acid prepared in Example 1, Example 2 and Comparative Example 1; Figure 8 This is a graph showing the lithium stability of the solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid prepared in Example 1; Fig. 9 is a cycle performance diagram of a lithium iron phosphate half-cell assembled from the solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid of Example 1; Fig.10 The LiNi is assembled from the solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid in Example 1. 0.88 Co 0.06 Mn 0.06 Cycling performance diagram of O2 half-cell. DETAILED DESCRIPTION

[0019] The technical solution of the present invention will be described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0020] Example 1 This embodiment provides a solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid, and the specific preparation steps are as follows: (1) Under argon atmosphere, dissolve 0.2 g (1.2 mmol) of p-fluorocinnamic acid in 8 mL of N-methylpyrrolidone and heat at 60°C with stirring until dissolved to obtain solution A.

[0021] (2) Under argon atmosphere, add 2 g (24 mmol) of vinylene carbonate monomer and 0.02 g of initiator azobisisobutyronitrile to solution A, heat and stir at 60 °C for 24 h to obtain solution B.

[0022] (3) Under argon atmosphere, add 1 g (3.6 mmol) of lithium bis(trifluoromethanesulfonyl imide) to solution B, heat and stir at 60°C until dissolved, to obtain solution C.

[0023] (4) Under argon atmosphere, 1.2 g (5.4 mmol) of poly(vinylidene fluoride-co-hexafluoropropylene) was added to solution C, and the mixture was heated and stirred at 60 °C for 24 h to obtain solution D.

[0024] (5) Solution D was coated on a polytetrafluoroethylene plate, and the solvent was evaporated by heating at 75 °C in a vacuum oven for 24 h to obtain a solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid. The obtained electrolyte membrane was cut into discs with a diameter of 16 mm.

[0025] In order to test the performance of the obtained polymer electrolyte membrane, the following battery was further assembled in this example: The specific preparation steps of the lithium symmetrical battery are as follows: assemble the battery negative electrode shell, the lithium metal sheet, the solid lithium ion battery polymer electrolyte membrane based on p-fluorocinnamic acid prepared in this embodiment, the lithium metal sheet, the gasket, the spring, and the battery positive electrode shell in order. Put the entire battery into a battery sealing machine and press it tightly to obtain a CR2032 button battery.

[0026] The specific preparation steps of the solid-state lithium-ion battery are as follows: assemble the battery negative electrode shell, lithium metal sheet, the solid-state lithium-ion battery polymer electrolyte membrane based on para-fluorocinnamic acid prepared in this embodiment, the positive electrode sheet, the gasket, the spring sheet, and the battery positive electrode shell in order. Put the entire battery into a battery sealing machine and press it tightly to obtain a CR2032 button battery. The preparation method of the positive electrode sheet is: lithium iron phosphate or LiNi0.88 Co 0.06 Mn 0.06 O2 powder, carbon black and polyvinylidene fluoride were ground in a mass ratio of 8:1:1, dispersed in N-methylpyrrolidone and stirred into slurry, then the slurry was coated on aluminum foil and placed in a forced air oven at 80°C for 16 hours. The dried electrode material was cut into discs with a diameter of 12 mm.

[0027] Example 2 This embodiment provides a solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid, and the specific preparation steps are as follows: (1) Under argon atmosphere, dissolve 0.2 g (1.2 mmol) of p-fluorocinnamic acid in 8 mL of N-methylpyrrolidone and heat at 60°C with stirring until dissolved to obtain solution A.

[0028] (2) Under argon atmosphere, 3 g (36 mmol) of vinylene carbonate monomer and 0.02 g of initiator azobisisobutyronitrile were added to solution A, and the mixture was heated and stirred at 60 °C for 24 h to obtain solution B.

[0029] (3) Under argon atmosphere, add 1 g (3.6 mmol) of lithium bis(trifluoromethanesulfonyl imide) to solution B, heat and stir at 60°C until dissolved, to obtain solution C.

[0030] (4) Under argon atmosphere, 1.2 g (5.4 mmol) of poly(vinylidene fluoride-co-hexafluoropropylene) was added to solution C, and the mixture was heated and stirred at 60 °C for 24 h to obtain solution D.

[0031] (5) Solution D was coated on a polytetrafluoroethylene plate, and the solvent was evaporated by heating at 75 °C in a vacuum oven for 24 h to obtain a solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid. The obtained electrolyte membrane was cut into discs with a diameter of 16 mm.

[0032] The lithium symmetrical battery and the solid-state lithium ion battery were assembled in the same manner as in Example 1.

[0033] Comparative Example 1 This comparative example provides a solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid, and the specific preparation steps are as follows: (1) Under argon atmosphere, dissolve 0.2 g (1.2 mmol) of p-fluorocinnamic acid in 8 mL of N-methylpyrrolidone and heat at 60°C with stirring until dissolved to obtain solution A.

[0034] (2) Under argon atmosphere, 4 g (48 mmol) of vinylene carbonate monomer and 0.02 g of initiator azobisisobutyronitrile were added to solution A, and the mixture was heated and stirred at 60 °C for 24 h to obtain solution B.

[0035] (3) Under argon atmosphere, add 1 g (3.6 mmol) of lithium bis(trifluoromethanesulfonyl imide) to solution B, heat and stir at 60°C until dissolved, to obtain solution C.

[0036] (4) Under argon atmosphere, 1.2 g (5.4 mmol) of poly(vinylidene fluoride-co-hexafluoropropylene) was added to solution C, and the mixture was heated and stirred at 60 °C for 24 h to obtain solution D.

[0037] (5) Solution D was coated on a polytetrafluoroethylene plate, and the solvent was evaporated by heating at 75 °C in a vacuum oven for 24 h to obtain a solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid. The obtained electrolyte membrane was cut into discs with a diameter of 16 mm.

[0038] The lithium symmetrical battery and the solid-state lithium ion battery were assembled in the same manner as in Example 1.

[0039] Figure 1 This is the infrared absorption spectrum of the solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid prepared in Example 1. Different characteristic peaks correspond to the structure of the target polymer, proving that various substances have been successfully introduced. Among them, the characteristic peaks corresponding to Ar-F, Ar-H, and C=O indicate that p-fluorocinnamic acid introduces fluorine atoms, benzene rings, and carboxyl groups into the electrolyte system. There is no characteristic peak corresponding to the carbon-carbon double bond (C=C) in the infrared absorption spectrum, indicating that the double bonds of the two monomers have undergone polymerization.

[0040] Figure 2 This is a surface SEM image of the solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid prepared in Example 1. It can be seen that the electrolyte surface is smooth and dense, which is conducive to good interface contact between the electrolyte membrane and the electrode.

[0041] Figure 3 This is a surface SEM image of the solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid prepared in Example 2. It can be seen that the smoothness of the electrolyte surface is slightly lower than that of Example 1, which will reduce the interface stability.

[0042] Figure 4 This is a surface SEM image of the solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid prepared in Comparative Example 1. It can be seen that the electrolyte surface is uneven, which leads to poor interface stability.

[0043] Figure 5The impedance diagram of the solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid prepared in Example 1, Example 2 and Comparative Example 1 is shown in FIG. Figure 5 According to formula (1), the room temperature ionic conductivity of the polymer electrolyte membrane prepared in Example 1 is 8.1×10 -4 S cm -1 The room temperature ionic conductivity of the polymer electrolyte membrane prepared in Example 2 is 7.1×10 -4 S cm -1 The room temperature ionic conductivity of the polymer electrolyte membrane prepared in Comparative Example 1 is 3.5×10 -4 Scm -1 .

[0044] (1) Where: σ is the ionic conductivity, unit is S cm -1 ; l is the thickness of the electrolyte membrane, in cm; R is the electrolyte membrane body impedance, in Ω; S is the electrolyte membrane area, in cm 2 .

[0045] Figure 6 The lithium ion migration number diagram of the solid-state lithium ion battery polymer electrolyte membrane based on p-fluorocinnamic acid prepared in Example 1 is shown in FIG. Figure 6 The data can be calculated according to formula (2) to obtain the room temperature lithium ion transfer number of the polymer electrolyte membrane prepared in Example 1, which is 0.69, indicating that most of the lithium ions in the lithium salt are dissociated from the anions, which is beneficial to improving ion transport.

[0046] (2) Where: is the lithium ion migration number; Δ V is the polarization voltage, set to 0.01 V; I 0 , I S is the initial current and the stable current, in A; R 0 , R S It is the interfacial impedance of the battery before and after polarization, in Ω. I 0 , I S 、R 0 , R S All can be obtained from Figure 6 Obtained in.

[0047] Figure 7 The electrochemical window diagrams of the solid-state lithium-ion battery polymer electrolyte membranes based on p-fluorocinnamic acid prepared in Example 1, Example 2 and Comparative Example 1 show that the electrochemical window of the polymer electrolyte membrane prepared in Example 1 is 5.40 V, the electrochemical window of the polymer electrolyte membrane prepared in Example 2 is 5.25 V, and the electrochemical window of the polymer electrolyte membrane prepared in Comparative Example 1 is 4.50 V. This shows that the electrolyte membrane is not only suitable for lithium iron phosphate positive electrodes, but also for LiNi 0.88 Co 0.06 Mn 0.06 O2 and other high voltage positive electrodes.

[0048] Figure 8 The lithium stability diagram of the solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid prepared in Example 1, with a current density of 0.2 mA / cm 2 The relatively stable voltage value distribution and 1200 h deposition / stripping behavior show that the electrolyte membrane has good lithium stability. This shows that the electrolyte membrane has good interface stability with lithium metal, which is beneficial to improve the cycle performance of lithium-ion batteries.

[0049] Fig. 9 This is a cycle performance diagram of a lithium iron phosphate half-cell assembled from the solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid in Example 1. Through cyclic charge and discharge tests, the operating voltage is 2.8-3.6 V, the discharge specific capacity is about 165 mAh / g at 1.0 C, and the coulombic efficiency is about 100%.

[0050] Fig.10 The LiNi is assembled from the solid-state lithium-ion battery polymer electrolyte membrane based on p-fluorocinnamic acid in Example 1. 0.88 Co 0.06 Mn 0.06 The cycle performance diagram of the O2 half-cell. Through the cyclic charge and discharge test, the operating voltage is 2.5-4.3 V, the discharge specific capacity is about 210 mAh / g at 0.2 C, and the Coulombic efficiency is about 90%.

[0051] The present invention does not elaborate on some of the common technologies of those skilled in the art. The above-described embodiments are only descriptions of preferred implementations of the present invention, and the preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementations described. Without departing from the design spirit of the present invention, various modifications and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the protection scope determined by the present invention.

Claims

1. A method for preparing a solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid, characterized in that: The steps include: (1) adding p-fluorocinnamic acid to a polar aprotic organic solvent, heating and stirring until dissolved, to obtain solution A; (2) adding a carbonate monomer and an initiator to solution A, heating and stirring to react, and obtaining solution B; (3) Add lithium salt to solution B, heat and stir until dissolved, and obtain solution C; (4) Add the polymer matrix to solution C, heat and stir until dissolved, and obtain solution D; (5) The solution D is coated on a polytetrafluoroethylene plate, and the solvent is dried under vacuum to obtain a solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid.

2. The method for preparing a solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid according to claim 1, characterized in that: Steps (1) to (4) are carried out in a normal pressure reactor protected by an inert gas atmosphere, the heating temperature is 40-80°C, and the heating and stirring reaction time in step (2) is 12-48 hours.

3. The method for preparing a solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid according to claim 1, characterized in that: The mass ratio of p-fluorocinnamic acid to polar aprotic organic solvent is 1:10-100; the molar ratio of p-fluorocinnamic acid to carbonate-based monomer is 1:1-30, the added amount of initiator is 0.05%-1% of the total mass of p-fluorocinnamic acid and carbonate-based monomer; the molar ratio of p-fluorocinnamic acid to lithium salt is 1:1-10; the molar ratio of p-fluorocinnamic acid to polymer matrix is ​​1:1-10.

4. The method according to claim 1, characterized in that: In step (1), the polar aprotic organic solvent is at least one of acetonitrile, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran and dichloromethane.

5. The method according to claim 1, characterized in that: In step (2), the carbonate-based monomer is at least one of vinylene carbonate, vinyl ethylene carbonate, ethyl methacrylate and methyl acrylate.

6. The method according to claim 1, characterized in that In step (3), the lithium salt is at least one of lithium nitrate, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(trifluoromethanesulfonylimide), lithium difluorooxalatoborate and lithium bis(fluorosulfonylimide).

7. The method according to claim 1, characterized in that In step (4), the polymer matrix is ​​at least one of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polyvinylidene fluoride and copolymers thereof.

8. A solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid, characterized in that: The solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid is prepared by the preparation method described in any one of claims 1 to 7.

9. A solid-state lithium-ion battery, characterized in that: A solid-state lithium-ion battery polymer electrolyte based on p-fluorocinnamic acid as claimed in claim 8.

Citation Information

Patent Citations

  • Preparation method and application of polycarbonate-based polymer electrolyte

    CN109802174A

  • Preparation and application of polycarbonate-based block polymer electrolyte

    CN110734517A

  • Solid polymer electrolyte membrane and preparation method thereof, solid-state battery and mechanical device

    CN119695269A

  • Polymer solid electrolyte and polymer solid electrolyte cell

    JP2003249266A

  • Phosphazene compound-based electrolyte compositions, quasi-solid and solid-state electrolytes, and lithium batteries

    US20220255129A1